Aplikasi Pencarian Rute Angkutan Umum Kota Malang Berbasis Android Berdasarkan Dua Titik Awal Terdekat - Almira Kalyana; Ratih Kartika Dewi; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Population increase occured in various regions of Indonesia, one of them is Malang City.With the increasing number of residents and immigrants of Malang City, then the public transportation is needed for the smoothness of their activities. Based on facts, media information for the pople of Malang City about public transportation routes is very needed. Currently, municipal government of Malang City is provides public transportation routes information on MediaCenter website. However, the information which provided is just a list of public transportation routes. So based the functional features, that information is not good enough to ease the user problem. Therefore, we need a mobile based application which built to facilitate residents and visitors of Malang City in choosing public transportation from the depature location to destination location. System was bulit using the haversine formula and best-path planning algorithm (hub-based planning). This system provides 2 starting points as an alternative to informing users that from the same depature site there are 2 starting points to get public transportation. The system scored 87% of accuracy testing on route search results. In usability testing, system earns 83% learnability, 62% efficiency, 91% memorability, 90% errors, and 88,5% statisfaction.